PERSEPSI MAHASISWA UKMI AR-ROYYAN UNIVERSITAS RIAU TERHADAP STIGMA TERORISME KELOMPOK ISLAM TERTENTU - Suci Ramadhani; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The background of the research is that terrorism cases continue to occur in Indonesia and some people accuse it of being masterminded by certain Islamic cohorts who carry out massive and coordinated movements in the community and academic circles, causimg Islamophobia. The formulation of the research problem is how the student of UKMI Ar-Royyan, Riau University perceive the stigma of terrorism of certain Islamic cohorts. The goal is to find out how the students of UKMI Ar-Royyan, Riau University perceive the stigma of terrorism of certain Islamic cohorts. Method used is quantitative with descriptive statiscal analysis techniques. The population in study were Riau University students who joined the Ar-Royyan UKMI in the 2020-2021 management. Sampling using the total sampling, amounting to 70 people. Based on the result of the study, the percentage of respondents’ alternative answers was 31,1 % wich was in the range of 25.01%-50% which was categorized as "not enough good". This shows that the perceptions of the students of UKMI Ar-Royyan University of Riau does not agree with the assumption/assessment that every use of Islamic symbols and attributes is stigmatized as perpetrators of terrorism shown in Islamic cohorts. However, the Ar-Royyan UKMI student at Riau University supports the government’s policy of banning certain cohorts that are indicated as terrorism.Key Words: perception, students, stigma of terrorism, Islamic cohort